Simultaneous Determination of Mineral Nutrients and Toxic Metals in M. stenopetala from Southern Ethiopia: A Comparative Study of Three Cultivating Areas Using MP-AES - Ashenafi Shemnsa; Wondimeneh Dubale Adane; Merid Tessema; Endale Tesfaye; Gizaw Tesfaye (Journal of Analytical Methods in Chemistry)
In this study, for the first time, the levels of thirteen micro- and macromineral nutrients in the leaves, seeds, and supportive soil of Moringa stenopetala (M. stenopetala) were simultaneously determined using microwave plasma atomic emission spectroscopy (MP-AES). The samples were collected during the arid season, in 2019 from the three main M. stenopetala growing areas in southern Ethiopia (Chano Mile Kebele, Nechisar Kebele, and Konso Special Woreda). A novel digestion method for leaf and seed samples was developed using an optimized acid mixture (2.5 : 0.75 : 0.5 of HNO3, HClO4, and H2O2) at 240°C for 2 hrs and 30 min, resulting in clear and colorless solutions. The method makes the digestion process more efficient by minimizing the reagent volume, reducing digestion temperature and time, and simplifying the overall procedure. The efficiency of the optimized procedure was validated by spiking experiments, and the percentage recovery ranged between 94 and 110%. Under optimized experimental conditions, higher concentrations of essential minerals (K, Na, Ca, and Mg) were observed in the plant leaf and seed samples from the three areas. In addition, significant amounts of trace elements (Fe, Mn, Zn, and Cu) were also found. Importantly, no traces of the toxic elements (Cd and Pb) were detected in any of the analyzed samples, suggesting that the leaves and seeds of M. stenopetala are valuable sources of both micro- and macromineral nutrients and are safe from toxic metals. From a dietary perspective, the seed contains almost comparable concentrations of minerals as the leaves. As a result, the seeds of M. stenopetala can serve as an alternative source of minerals and play a role in overcoming the current global food crisis, particularly in the dry season. Analysis of variance at a 95% confidence level revealed significant differences in the levels of all mineral nutrients between the three sample means except K, Ca, Co, and Cu. Generally, the developed method includes an innovative digestion procedure that minimizes reagent consumption, operates at lower temperatures, and requires shorter digestion times, thereby optimizing resource utilization and maintaining analytical accuracy. Notably, the absence of toxic elements in the MP-AES procedure highlights the safety and reliability of M. stenopetala leaves and seeds as valuable, contamination-free sources of essential nutrients.